Production of malagueta pepper seedlings in response to different seeding depths and containers (Research, Society and Development, 2022)
This work aimed to determine the ideal sowing depth and container for the production of chili pepper seedlings. The work was carried out in the municipality of Palmeira-PR between January and February 2022. The chili pepper seedlings were conducted in a protected place with white shade and manual irrigation. The determined treatments were implemented in a completely randomized design in a 2X3 factorial scheme, where the first factor corresponded to the two containers used (polystyrene tray and plastic bags), and three sowing depths (0, 1 and 2 cm), with four replications. per treatment and 4 seedlings per repetition. The variables were analyzed 37 days after sowing, evaluating: number of leaves, stem diameter, plant height, root length and percentage of emergence. There was a significant interaction between the factors in all analyzed variables; only the percentage of emergence showed an isolated effect of sowing depth. It is recommended to produce chili pepper seedlings in plastic bags (3000 cm³) and with their seeds sown in depths of 1 or 2 cm, as they present desirable vegetative characteristics of better quality when compared to trays of 72 cells (121.2 cm³) and superficial seeding depth of 0 cm.